2019
DOI: 10.1104/pp.19.00119
|View full text |Cite
|
Sign up to set email alerts
|

CALMODULIN-BINDING TRANSCRIPTION ACTIVATOR 6: A Key Regulator of Na+ Homeostasis during Germination

Abstract: Salinity impairs seed germination and seedling establishment. We investigated the role of Arabidopsis (Arabidopsis thaliana) CALMODULIN-BINDING TRANSCRIPTION ACTIVATOR 6 (CAMTA6) in salinity stress responses during early germination. Compared with the wild type, the camta6-4 and camta6-5 mutants were more tolerant to NaCl and abscisic acid (ABA) and accumulated less Na +. In contrast, 4-to 11-d-old camta6 seedlings were more sensitive to NaCl. In camta6, expression of HIGH-AFFINITY K + TRANSPORTER1 (AtHKT1;1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 101 publications
1
48
0
Order By: Relevance
“…For instance, AtCAMTA1 and AtCAMTA3 play roles against freezing and drought stress as well as regulation of auxin and salicylic acid in plants [31][32][33][34][35]. AtCAMTA6 support the plants against salt stress, while AtCAMTA4 performs pivotal role in defense responses of plants against Puccinia triticina and low temperature stress [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, AtCAMTA1 and AtCAMTA3 play roles against freezing and drought stress as well as regulation of auxin and salicylic acid in plants [31][32][33][34][35]. AtCAMTA6 support the plants against salt stress, while AtCAMTA4 performs pivotal role in defense responses of plants against Puccinia triticina and low temperature stress [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…This increase in germination could be explained by reduced sodium uptake by the germinating seed, observed for two independent camta6 alleles. Interestingly, Shkolnik et al (2019) observed that decreased sodium accumulation corresponded to the repressed expression of high-affinity K + transporter (AtHKT1) known to import sodium ions into the root pericycle from the vasculature, thereby limiting sodium accumulation in the shoot (Mäser et al, 2002;Møller et al, 2009). The levels of AtHKT1 were not induced in response to salt stress in camta6 lines, and AtHKT1 expression was also limited to the radicle and excluded from developing cotyledons.…”
Section: Changing Gears In Salt Stress Tolerance: Atcamta6's Role Inmentioning
confidence: 99%
“…Another exciting aspect of the work described by Shkolnik et al (2019) is that although camta6 seedlings outperformed wild-type lines during germination under salt stress, reduced salt stress tolerance was observed for the mutants at later developmental stages. This phenomenon could be explained by camta6 lines' inability to induce AtHKT1 expression.…”
Section: Changing Gears In Salt Stress Tolerance: Atcamta6's Role Inmentioning
confidence: 99%
“…Calmodulin-binding transcription activators (CAMTAs) are a highly conserved family of Ca 2+ -regulated transcription factors 1 . In plants, CAMTAs are transcriptional effectors of Ca 2+ /CaM signaling in response to biotic/abiotic stress [2][3][4][5][6] . Mammals encode two CAMTA proteins that are enriched in heart and brain tissue 7 .…”
Section: Introductionmentioning
confidence: 99%